2002
DOI: 10.1002/em.10070
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to heterocyclic amine food mutagens/carcinogens: Relevance to breast cancer

Abstract: Heterocyclic amines produced from overcooked foods are extremely mutagenic in numerous in vitro and in vivo test systems. One of these mutagens, 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP), induces breast tumors in rats and has been implicated in dietary epidemiology studies as raising the risk of breast cancer in humans. Efforts in our laboratory and others have centered on defining the exposure to PhIP and other dietary mutagens derived from cooked food. We accomplish this by analyzing the foods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 45 publications
0
56
0
3
Order By: Relevance
“…The compounds were found to be extremely mutagenic agents in numerous in vitro and in vivo systems; they are able to increase breast cancer risk (Zheng et al, 1998;Felton et al, 2002). Knize and co-workers (1985; observed that concentration of these carcinogens depends on cooking method, time, temperature and protein source.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds were found to be extremely mutagenic agents in numerous in vitro and in vivo systems; they are able to increase breast cancer risk (Zheng et al, 1998;Felton et al, 2002). Knize and co-workers (1985; observed that concentration of these carcinogens depends on cooking method, time, temperature and protein source.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Daily human intakes of HCAs, estimated to be ∼60 ng/day, 7 are modest; however, exposure to these compounds, which have been isolated from human urine, 8 is of concern with regard to human health.…”
Section: F]quinoline (Iq) 1-4mentioning
confidence: 99%
“…Several studies have shown that colorectal cancer cases are more likely to be rapid acetylators if they consume diets high in red meat intake. 10 In some, but not all, studies that assessed exposure to heterocyclic amines by using information on meat intake, and preferred methods of cooking the meat (eg, grilling versus broiling versus roasting), 49 rapid acetylators consuming higher predicted heterocyclic amine intake have again been at somewhat higher risk of colorectal cancer. Studies such as these can help identify the specific human carcinogens in complex mixtures, like diet, and may ultimately lead to preventive advice for populations (eg, changes in meat cooking practices) or individuals (eg, those with susceptibility genotypes for common environmental exposures).…”
Section: Susceptibility Genes: Carcinogen Metabolism and Detoxificatimentioning
confidence: 99%